Identification and expression of bifunctional acid urea‐degrading enzyme/urethanase from Enterobacter sp. R‐SYB082 and its application in degradation of ethyl carbamate in Chinese rice wine (Huangjiu). (16th March 2022) - Zheng, Huajun; Meng, Kai; Liu, Jun; Lin, Zichen; Peng, Qi; Xie, Guangfa; Wu, Peng; Elsheery, Nabil Ibrahim
Abstract: BACKGROUND: Ethyl carbamate (EC) is a potential carcinogen existing in fermented foods such as Chinese rice wine ( Huangjiu ). Since urea is an important precursor of EC, the degradation of urea could be an effective way to reduce EC in foods. RESULTS: In this study, an Enterobacter sp. R‐SYB082 with acid urea degradation characteristics was obtained through microbial screening. Further research isolated a new acid urea‐degrading enzyme from R‐SYB082 strain – ureidoglycolate amidohydrolase (UAH) – which could degrade EC directly. The cloning and expression of UAH in Escherichia coli BL21 (DE3) suggested that the activity of urea‐degrading enzyme reached 3560 U L −1, while urethanase activity reached 2883 U L −1 in the optimal fermentation condition. The enzyme had the dual ability of degrading substrate urea and product EC. The removal rate of EC in Chinese rice wine could reach 90.7%. CONCLUSION: This study provided a new method for the integrated control of EC in Chinese rice wine and other fermented foods. © 2022 Society of Chemical Industry.